2013
DOI: 10.1074/jbc.m112.407676
|View full text |Cite
|
Sign up to set email alerts
|

Transport of the GlcNAc-1-phosphotransferase α/β-Subunit Precursor Protein to the Golgi Apparatus Requires a Combinatorial Sorting Motif

Abstract: Background: Golgi-resident GlcNAc-1-phosphotransferase is the key enzyme for biosynthesis of mannose 6-phosphate recognition marker. Results: Identification of a combinatorial ER export motif in the N-and C-terminal cytosolic domains of the GlcNAc-1-phosphotransferase ␣/␤-subunit precursor protein.Conclusion: COPII-dependent ER export of the phosphotransferase precursor is mediated by dileucine/dibasic sorting motifs. Significance: Novel insights into ER sorting of type III membrane proteins are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…The two cytosolic domains of GNPTAB at the N-and C-termini contain motifs that mediate the export or trafficking of the enzyme through the endoplasmic reticulum and Golgi. The importance of the N-terminal domain has been highlighted by recent work from Franke et al 15 showing that the lysine residue at position 4-the same residue mutated in the patients described in this report-affects a neighboring dileucine sequence responsible for the export of the GlcNAc-1-phosphotransferase ab precursor from the endoplasmic reticulum. 15 The possibility that other mutations may be found to result in an identical phenotype cannot be excluded.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The two cytosolic domains of GNPTAB at the N-and C-termini contain motifs that mediate the export or trafficking of the enzyme through the endoplasmic reticulum and Golgi. The importance of the N-terminal domain has been highlighted by recent work from Franke et al 15 showing that the lysine residue at position 4-the same residue mutated in the patients described in this report-affects a neighboring dileucine sequence responsible for the export of the GlcNAc-1-phosphotransferase ab precursor from the endoplasmic reticulum. 15 The possibility that other mutations may be found to result in an identical phenotype cannot be excluded.…”
Section: Discussionmentioning
confidence: 69%
“…The importance of the N-terminal domain has been highlighted by recent work from Franke et al 15 showing that the lysine residue at position 4-the same residue mutated in the patients described in this report-affects a neighboring dileucine sequence responsible for the export of the GlcNAc-1-phosphotransferase ab precursor from the endoplasmic reticulum. 15 The possibility that other mutations may be found to result in an identical phenotype cannot be excluded. It remains to be seen whether other mutations within the N-terminal domain, or perhaps the C-terminal cytosolic domain, are associated with the unique clinical and biochemical features described in the patients reported here.…”
Section: Discussionmentioning
confidence: 69%
“…It will be of interest to find out whether GOLPH3 interacts with other glycosyltransferases in the Golgi. Recently, Franke and colleagues reported that the K4Q mutation impaired a 5 LL 6 -dependent ER export signal in the N-terminal tail of αβ phosphotransferase (20). This was based on the finding that the level of mature β subunit was decreased relative to the αβ precursor, as detected by Western blotting and the accumulation of the mutant in the ER by immunofluorescence microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported an expression analysis of a missense mutation p.Lys4Gln found homozygously in a mildly affected MLIII alpha/beta patient [Franke et al., ]. This mutation reduces the GlcNAc‐1‐phosphotransferase activity to 12% of controls [Kudo et al., ].…”
Section: Discussionmentioning
confidence: 99%